Formation of the Philtral Column Using a Dermal Graft in Secondary Unilateral Cleft Lip. Issue 7 (October 2017) - Kim, Jeenam; Park, Jongok; Uhm, Ki-il; Shin, Donghyeok; Choi, Hyungon
Abstract : Introduction: The philtral column has an important aesthetic significance and is especially important in patients with cleft lip. If the integrity of the philtrum cannot be preserved in patients of unilateral clefts, these patients will have profound abnormalities in their facial musculature. The purpose of this study was to analyze the effects of dermal grafting on the philtral column in patients with a unilateral alveolar cleft. Methods: The authors retrospectively studied dermal grafts performed in Konkuk University Medical Center between January 2009 and January 2015. A total of 26 patients with unilateral cleft lip were included in this study; the authors measured philtral symmetry based on differences in convexity and angle using clinical photos. Additionally, panel evaluation was performed. Results: Of 26 patients enrolled, 21 completed follow-up and had adequate photographs. Five patients who were lost to follow-up were excluded. The difference in convexity decreased from 0.25 to 0.15 ( P < 0.005) and the difference in angle decreased from 10.76 to 6.43 ( P < 0.005). The panel evaluation indicated that patient appearances were significantly improved ( P < 0.001). Discussion: In patients with secondary cleft lip deformity of the philtral depression, the authors' procedure may augment the thickness of the philtral ridge and have positive aesthetic outcomes.